The Influence of Social Media Marketing, Digital Content Quality and Customer Trust on Brand Awareness: A Study of the Just Hebite MSME in Banjarnegara - Novika Khusnul Chotimah; Jaya Ramaeday Bangsa (International Forum of Researchers and Lecturers, 2026)
The rapid growth of internet and social media penetration in Indonesia has transformed marketing activities from conventional approaches into interactive digital marketing, particularly among Micro, Small, and Medium Enterprises (MSMEs). Just Hebite, an MSME producing modified cassava flour (mocaf)-based food products in Banjarnegara, Central Java, faces challenges in building brand awareness due to the public's limited familiarity with mocaf-based products compared to wheat flour, alongside the still-developing use of social media marketing. This study aims to examine and analyze the influence of social media marketing, digital content quality, and customer trust on brand awareness of the Just Hebite MSME. A quantitative explanatory research design was employed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. Data were collected through a structured questionnaire using a five-point Likert scale distributed to 104 respondents, determined through purposive sampling from consumers who follow Just Hebite's Instagram account, have been exposed to its social media content, and/or have purchased its products. [Results of hypothesis testing (H1-H3) — pending completion of the outer and inner model analysis in SmartPLS 4.] The findings are expected to provide theoretical contributions to digital marketing literature, particularly regarding brand awareness formation among local, education-based MSME products, and practical contributions for Just Hebite in strengthening its digital marketing strategy.